مقصد حفظ الدّين من خلال جيود جمعية العمماء المسممين - عبد المجيػد بطة; د/الشطة مصطفى (جامعة عمار ثليجي الاغواط, 2023)
ممخص الد ا رسة: العنوان: مقصد حفظ الدين من خلال جيود جمعية العمماء المسممين د ا رسة تطبيقية - - ييدؼ البحث إلى إب ا رز جيكد جمعية العمماء المسمميف الج ا زئرييف في حفظ مقصد الديف ، الذم ىك أكٍلى المقاصد كأعلاىا، فيك محكر حياة الإنساف كسبب كجكده، كالحكمة مف خمقو، كسر سعادتو في الدنيا كالآخرة ، فقامت بحفظو مف خلاؿ تصرفاتي كفتاكيي ككتاباتي التي كانت تصرفات مقصكدة ، كغايات مرجكة ، برعايتو كاعماؿ فقو المآلات كالأكلكيات كسد الذ ا رئع فيو.. ،كذالؾ بحفظو مف جانبي الكجكد كالعد بالتطبيؽ كالتنزيؿ،حيث إحتكل الفصؿ التمييدم عمى ق ا رءة تاريخية لضركؼ نشأة الجمعية ، كاختيار منيجيا ،كجيكدىا في تبييف الديف الصحيح كنشره، كبالتحذير مما ييدمو، مع ذكر مختمؼ المكاقؼ،بينما الفصؿ الثاني كاف لمتعريؼ بعم المقاصد كتطكره كأبرز عممائو كتقسيماتو،ث ذكر مقصد حفظ الديف مف جانبي الكجكد كالعد، كفصؿ تطبيقي أخير إستقصيت فيو المكاقؼ كحممتيا ، كضربت الأمثمة كفسرتيا، كبينت اف جيكد الجمعية لحفظ الديف مف جانبي الكجكد كالعد ،كانت بالتطبيؽ كالتنزيؿ كليس بالتأصيؿ كالتنظير، كخت الد ا رسة بنتائج كتكصيات. Research Summary: Title: The purpose of preserving religion through the efforts of the Association of Muslim Scholars - an applied study - The research aims to highlight the efforts of the Association of Algerian Muslim Scholars in preserving the purpose of religion, which is the first and highest purposes, it is the focus of human life and the reason for its existence, and the wisdom of his creation, and the secret of his happiness in this world and the hereafter, so it saved it through their actions, fatwas and writings, which were intentional actions, and desired goals, by sponsoring it and implementing the jurisprudence of outcomes and priorities and blocking the pretexts in it. The introductory chapter contained a historical reading of the circumstances of the emergence of the association, and the choice of its approach, and its efforts in showing the correct religion and disseminating it, and warning of what destroys it, with the mention of various positions, while the second chapter was to introduce the science of purposes and its development and the most prominent scholars and divisions, then mentioned the purpose of preserving religion from the sides of existence and nothingness, and a final applied chapter in which the positions were investigated and analyzed, and examples were struck and interpreted, and showed that the association's efforts to preserve religion from both sides of existence and nothingness, were by application and download and not by rooting and endoscopy, and concluding the study with results and recommendations.